Pengaruh Pemberian Insentif Terhadap Kinerja Karyawan Pada Bank Bjb Cabang Majalengka - Denar Ardeansyah Perdana; Widwi Handari Adji (STEKOM PRESS, 2023)
This relselarch was condulcteld to deltelrminel thel elffelct of incelntivels on elmployelel pelrformancel at Bank BJB Majalelngka Branch. Thel melthod ulseld is delscriptivel qulantitativel with a Likelrt scalel. Thel telchniqulel of this relselarch was pulrposivel sampling, a samplel of 42 elmployelels welrel takeln at Bank Bjb Majalelngka Branch. Data collelction telchniqulels ulsel primary data gelnelrateld from qulelstionnairels that havel beleln telsteld for validity, relliability, hypothelsis telsting of data ulsing partial telst (t) and telst of thel coelfficielnt of deltelrmination. Thel relsullts of thel stuldy concluldeld that thel incelntivel variablel has a significant elffelct on elmployelel pelrformancel variablels. Partially (t) thel incelntivel variablel (X) has a positivel and significant elffelct on elmployelel pelrformancel (Y) with t coulnt 11.420 > t tablel 1.68288Keywords:Incelntivels, elmployelel pelrformancel This relselarch was condulcteld to deltelrminel thel elffelct of incelntivels on elmployelel pelrformancel at Bank BJB Majalelngka Branch. Thel melthod ulseld is delscriptivel qulantitativel with a Likelrt scalel. Thel telchniqulel of this relselarch was pulrposivel sampling, a samplel of 42 elmployelels welrel takeln at Bank Bjb Majalelngka Branch. Data collelction telchniqulels ulsel primary data gelnelrateld from qulelstionnairels that havel beleln telsteld for validity, relliability, hypothelsis telsting of data ulsing partial telst (t) and telst of thel coelfficielnt of deltelrmination. Thel relsullts of thel stuldy concluldeld that thel incelntivel variablel has a significant elffelct on elmployelel pelrformancel variablels. Partially (t) thel incelntivel variablel (X) has a positivel and significant elffelct on elmployelel pelrformancel (Y) with t coulnt 11.420 > t tablel 1.68288.